2023
DOI: 10.1055/a-2085-1429
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dual-task Gait Speed in Older Adults with and without Parkinson’s Disease

Abstract: Mobility difficulties for people with Parkinson’s disease (PwPD) are more pronounced when they perform a simultaneous cognitive task while walking. Although it is known that neurodegeneration results in widespread motor and brain impairments, few studies have comprehensively examined possible physical and mental determinants of dual task walking in PwPD. In this cross-sectional study, we aimed to investigate if and how muscle strength (sit-to-stand 30s test), cognition (mini-mental state examination) and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Significantly, these results show a more pronounced increase in ∆ TUGT% among IDG participants compared to TDG participants. This finding aligns with a previous study involving older adults with Parkinson's disease, where, when presented with a dual task, they demonstrated a significant reduction in walking speed compared to older adults without Parkinson's disease [7]. In both cases, the dual-task scenario and the shared impact on dynamic balance underscore the common challenges individuals with specific conditions face when multitasking during walking.…”
Section: Dynamic Balancesupporting
confidence: 90%
See 1 more Smart Citation
“…Significantly, these results show a more pronounced increase in ∆ TUGT% among IDG participants compared to TDG participants. This finding aligns with a previous study involving older adults with Parkinson's disease, where, when presented with a dual task, they demonstrated a significant reduction in walking speed compared to older adults without Parkinson's disease [7]. In both cases, the dual-task scenario and the shared impact on dynamic balance underscore the common challenges individuals with specific conditions face when multitasking during walking.…”
Section: Dynamic Balancesupporting
confidence: 90%
“…However, when adolescents engage in multiple tasks simultaneously, a phenomenon known as dual-tasking postural control [6], their postural balance can be compromised due to divided attention. Previous research has explored dual-task models, particularly in the context of aging and neurodegenerative diseases, shedding light on the intricate interplay between cognitive and motor functions [7]. Furthermore, several studies have demonstrated that individuals with intellectual disabilities, including children and adults, experience alterations in postural balance when simultaneously engaging in supplementary tasks, affecting both static [6,8] and dynamic [9][10][11] balance compared to their counterparts with typical development.…”
Section: Introductionmentioning
confidence: 99%